90Sr spectrometry - M. D. Bondarkov; V. О. Zheltonozhsky; D. E. Myznikov; A. M. Savrasov; V. I. Slisenko; M. V. Strilchuk (Ядерна фізика та енергетика)
A spectroscopic method has been developed based on measuring of beta-spectra, which takes into account the physico-chemical state of the investigated objects and the instability of electronic systems in field conditions. This method allows for the investigation of the 90Sr and 137Cs concentration in various objects with a change in the 137Cs/90Sr ratio from 1 to 100 with an error of better than 20 %. A methodology has been developed that takes into account the change in the density of the inanimate objects and is based on shifting of the peak position of the conversion electrons from the 137Cs decay. The verification of the methodology compared to radiochemical measurements of 90Sr in soil samples showed complete agreement within 10 - 15 %, with a change of the activity in the samples by four orders of magnitude.